Geometria analítica: articulando registros algébricos e geométricos com o GrafEq - Martinelli, Diego da Silva Pinto (2017)
In this dissertation an investigation and the creation of a didactic proposal for the teaching of Analytical Geometry in computerized environments were developed, that could allow to the students to explore the algebraic and geometric registers with the use of GrafEq, propitiating the articulation between them. In this regard, our teaching sequence was elaborated in light of Raymond Duval's theory of semiotic representation records. We use didactic engineering as a research methodology, which values both the theoretical and the experimental aspects, ie articulates research and didactic action, as well as providing an organization in the work structure. It is hoped that the didactic sequence in computerized environments can contribute to the student's understanding of geometric concepts, expanding his knowledge. Our research environment was a group of the third year of high school, of the public network of Porto Alegre. It was verified that, after the sequence of teaching of the content of analytical geometry in computerized environments, the students presented themselves more critical and able to discuss in groups to form a consensual opinion in the resolution of problems, besides recognizing geometric elements in their registers algebraic and vice versa.